4
$\begingroup$

The integral:

$$\int_0^{+\infty} \frac{x^2+1}{x^4+1}dx$$

If num were greater than denum I would just devide it normally with long division, but it is not, how should I handle it then?

$\endgroup$
  • 2
    $\begingroup$ Hint: $x^4 + 1 = (x^4 + 2x^2 + 1) - 2x^2 = (x^2+1)^2 - (x\sqrt{2})^2 = (x^2 + x\sqrt{2} + 1) (x^2 - x\sqrt{2} + 1)$. $\endgroup$ – Daniel Schepler May 22 '17 at 21:17
  • 3
    $\begingroup$ "How to take"? What does that mean? To decide whether it converges or not, or to evaluate it? $\endgroup$ – DonAntonio May 22 '17 at 21:20
  • $\begingroup$ Here is your answer: wolframalpha.com/input/… $\endgroup$ – Crostul May 22 '17 at 21:22
  • $\begingroup$ @DonAntonio i think the OP wants to compute the result exactly... $\endgroup$ – gt6989b May 22 '17 at 21:24
  • $\begingroup$ @gt6989b I'd rather have the OP to have the good manners to address doubts about his ill-posed question . I don't usually like guessing. $\endgroup$ – DonAntonio May 22 '17 at 21:25
9
$\begingroup$

Whenever I see an integrand that is sort of symmetric under $x \to x^{-1}$, I will try to see whether I can express the intergrand in terms of $x \pm x^{-1}$. Using following identities, $$\frac{dx}{x} = \frac{d(x-x^{-1})}{x+x^{-1}} = \frac{d(x+x^{-1})}{x-x^{-1}}$$ we find $$\begin{align} \int_0^\infty \frac{x^2+1}{x^4+1}dx &= \int_0^\infty \frac{x+x^{-1}}{x^2+x^{-2}} \frac{dx}{x} = \int_0^\infty \frac{x+x^{-1}}{x^2+x^{-2}} \frac{d(x-x^{-1})}{x+x^{-1}} = \int_0^\infty \frac{d(x-x^{-1})}{(x-x^{-1})^2+2}\\ &= \int_{-\infty}^\infty \frac{dy}{y^2+2} = \left[\frac{1}{\sqrt{2}}\tan^{-1}\frac{y}{\sqrt{2}}\right]_{-\infty}^\infty = \frac{\pi}{\sqrt{2}} \end{align} $$

$\endgroup$
  • 1
    $\begingroup$ Now that's a sneaky, nice argument! +1 I'd rather do this by complex integration $\endgroup$ – DonAntonio May 22 '17 at 21:31
  • $\begingroup$ @DonAntonio But its always quite fun to see these simple elementary solutions done beautifully. $\endgroup$ – Simply Beautiful Art May 22 '17 at 21:35
  • 2
    $\begingroup$ @DonAntonio I think people are running out of idea to create hard looking but easy to compute integral. This is the third (or fourth?) time this week I answered question using this trick! It start to become automatic.... $\endgroup$ – achille hui May 22 '17 at 21:39
5
$\begingroup$

$$\int_{0}^{1}\frac{x^2+1}{x^4+1}\,dx + \int_{1}^{+\infty}\frac{x^2+1}{x^4+1}\,dx = 2\int_{0}^{1}\frac{1+x^2}{1+x^4}\,dx = 2\int_{0}^{1}\frac{1+x^2-x^4-x^6}{1-x^8}\,dx$$ hence the value of the integral is provided by the (Dirichlet) series $$ 2\sum_{k\geq 0}\left(\frac{1}{8k+1}+\frac{1}{8k+3}-\frac{1}{8k+5}-\frac{1}{8k+7}\right) $$ that can be computed through the digamma reflection formula. Its value is just $$ \boxed{I = \color{red}{\frac{\pi}{\sqrt{2}}}} .$$ The given integral is straightforward to compute through the residue theorem, too.

$\endgroup$
4
$\begingroup$

By symmetry,

$$2\int_0^{+\infty}\frac{x^2+1}{x^4+1}\ dx=\int_{-\infty}^{+\infty}\frac{x^2+1}{x^4+1}\ dx$$

By taking a semi-circle contour in the upper half of the complex plane and applying Cauchy's residue formula, we find that

$$\begin{align}\int_{-\infty}^{+\infty}\frac{x^2+1}{x^4+1}\ dx&=2\pi i\left[\lim_{a\to e^{\pi i/4}}\frac{(a^2+1)(a-e^{\pi i/4})}{a^4+1}+\lim_{b\to e^{3\pi i/4}}\frac{(b^2+1)(b-e^{3\pi i/4})}{b^4+1}\right]\\&=2\pi i\left[\frac{1+i}{4e^{3\pi i/4}}+\frac{1-i}{4e^{9\pi i/4}}\right]\\&=\frac{\pi i}{2\sqrt2}\left[(1-i)^2-(1+i)^2\right]\\&=\sqrt2\pi\end{align}$$

Thus,

$$\int_0^{+\infty}\frac{x^2+1}{x^4+1}\ dx=\frac{\sqrt2\pi}2=\frac\pi{\sqrt2}$$

$\endgroup$
2
$\begingroup$

$\newcommand{\bbx}[1]{\,\bbox[8px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$ $\Huge\left.a\right)$

With $\ds{p \equiv \exp\pars{{\pi \over 4}\,\ic}}$ and integrating in a quarter circle in the first quadrant:

\begin{align} \int_{0}^{\infty}{x^{2} + 1 \over x^{4} + 1}\,\dd x & = \Re\pars{2\pi\ic\,\lim_{x \to p}{\bracks{x\vphantom{^{2}} - p}\bracks{x^{2} + 1} \over x^{4} + 1}} \label{1}\tag{1} \\[5mm] & = \Re\pars{2\pi\ic\,\lim_{x \to p}{x^{3} - px^{2} + x - p \over x^{4} + 1}} \\[5mm] & = -2\pi\,\Im\pars{\lim_{x \to p}{3x^{2} - 2px + 1 \over 4x^{3}}} = -\,{\pi \over 2}\,\Im\pars{\lim_{x \to p}{3x^{3} - 2px^{2} + x \over x^{4}}} \\[5mm] & = {\pi \over 2}\,\Im\pars{p^{3} + p} = {\pi \over 2}\,\Im\pars{p^{2}\bracks{p + {1 \over p}}} = {\pi \over 2}\,\Im\pars{\ic\bracks{2\cos\pars{\pi \over 4}}} \\[5mm] & = \bbx{{\root{2} \over 2}\,\pi} \end{align}

In \eqref{1},

  • I omitted the integration along the imaginary axis because its real part vanishes out.

  • The integral along the arc, of radius $\ds{R}$, is of $\ds{\,\mrm{O}\pars{1 \over R}}$ as $\ds{R \to \infty}$ such that it vanishes out in such a limit.


$\Huge\left.b\right)$

With $\ds{\Lambda > 0}$:

\begin{align} \int_{0}^{\infty}{x^{2} + 1 \over x^{4} + 1}\,\dd x & = \lim_{\Lambda \to \infty}\int_{0}^{\Lambda}{x^{2} + 1 \over x^{4} + 1}\,\dd x = \Im\lim_{\Lambda \to \infty}\int_{0}^{\Lambda}{x^{2} + 1 \over x^{2} - \ic} \,\dd x \\[5mm] & = \Im\pars{\bracks{1 + \ic}\lim_{\Lambda \to \infty} \int_{0}^{\Lambda}{\dd x \over x^{2} - \ic}} \\[5mm] & = \Im\pars{{1 + \ic \over 2\root{i}}\lim_{\Lambda \to \infty}\int_{0}^{\Lambda}\bracks{% {1 \over x - \root{\ic}} - {1 \over x + \root{\ic}}}\dd x} \\[5mm] & = {1 \over 2}\, \Im\pars{\bracks{\expo{-\ic\pi/4} + \expo{\ic\pi/4}}\bracks{\pi\ic}} = \bbx{{\root{2} \over 2}\,\pi} \end{align}

$\endgroup$
  • $\begingroup$ @user1892304 Thanks. By the way, they are concise answers too !!!. $\endgroup$ – Felix Marin May 26 '17 at 17:20
1
$\begingroup$

Substituting $x = t^{\frac{1}{4}}$ yields the integral:

$$\frac{1}{4}\int_0^{\infty}\frac{x^{-\frac{1}{4}} + x^{-\frac{3}{4}}}{1+x}dx=\frac{\pi}{2\sin\left(\frac{\pi}{4}\right)}=\frac{\pi}{\sqrt{2}}$$

where we've used the result:

$$\int_0^{\infty}\frac{x^{-p}}{1+x}dx=\frac{\pi}{\sin(\pi p)}$$

This can be proven using contour integration, see page 12 of this document.

$\endgroup$
1
$\begingroup$

By substituting $x\mapsto\frac1x$, we get $$ \int_0^1\frac{x^2+1}{x^4+1}\,\mathrm{d}x=\int_1^\infty\frac{x^2+1}{x^4+1}\,\mathrm{d}x $$ Therefore, using formula $(6)$ from this answer, we get $$ \begin{align} \int_0^\infty\frac{x^2+1}{x^4+1}\,\mathrm{d}x &=2\int_0^1\frac{x^2+1}{x^4+1}\,\mathrm{d}x\\ &=2\int_0^1\left(1+x^2-x^4-x^6+x^8+x^{10}-x^{12}-x^{14}+\cdots\right)\,\mathrm{d}x\\ &=2\left(1+\frac13-\frac15-\frac17+\frac19+\frac1{11}-\frac1{13}-\frac1{15}+\cdots\right)\\ &=2\sum_{k=1}^\infty\left(\frac1{8k-7}+\frac1{8k-5}-\frac1{8k-3}-\frac1{8k-1}\right)\\ &=\frac14\sum_{k=1}^\infty\left[\left(\tfrac1k-\tfrac1{k-\frac18}\right)+\left(\tfrac1k-\tfrac1{k-\frac38}\right)-\left(\tfrac1k-\tfrac1{k-\frac58}\right)-\left(\tfrac1k-\tfrac1{k-\frac78}\right)\right]\\ &=\frac14\left(\color{#C00}{H_{-\frac18}}+\color{#090}{H_{-\frac38}-H_{-\frac58}}\color{#C00}{-H_{-\frac78}}\right)\\[4pt] &=\frac\pi4\left(\color{#C00}{\cot\left(\frac\pi8\right)}+\color{#090}{\cot\left(\frac{3\pi}8\right)}\right)\\[5pt] &=\frac\pi{\sqrt2} \end{align} $$ Since $\cot\left(\frac\pi8\right)=\sqrt2+1$ and $\cot\left(\frac{3\pi}8\right)=\sqrt2-1$.

$\endgroup$
0
$\begingroup$

The function integrand is positive.

By equivalence test

Near zero, no problem.

Near $+\infty, $ we have

$$\frac {x^2+1}{x^4+1}\sim \frac {x^2}{x^4}\sim \frac {1}{x^2} .$$

thus it Converges.

Or by comparison test

for great enough $x $

$$\frac {x^2+1}{x^4+1}\leq \frac {2x^2}{x^4} =\frac {2}{x^2}$$

$\endgroup$
  • 1
    $\begingroup$ This assumes the questioner needs to decide convergence and nothing else. $\endgroup$ – Matthew Leingang May 22 '17 at 21:21

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.